Unveiling the ESIPT Luminescence Mechanism of 4′-N,N-Diethylamino-3-Hydroxyflavone in Ionic Liquid: A Computational Study - Jin Yang; Qi Li; Meilin Guo; Lu Yan; Lixia Zhu; Jing Zhao; Guangxiong Hu; Hang Yin; Ying Shi (Molecules)
Excited state intramolecular proton transfer (ESIPT) within molecules in solvents plays important roles in photo-chemistry and photo-biology. Herein, the influence of 1-ethyl-3-methyl-imidazolium bis (trifluoromethylsulfonyl) imide ([EMIm][NTf2]) and 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIm][PF6]) on the ESIPT of 4′-N,N-diethylamino-3-hydroxyflavone (DEAHF) was explored. The density functional theory and time-dependent density functional theory methodologies were used. The calculated fluorescence spectrum reveals that the fluorescence peaks of DEAHF in [EMIm][NTf2] and [BMIm][PF6] originate from the emission of N* and T* forms. The structure’s optimization, infrared spectra, non-covalent interactions and the scanning of potential energy curves collectively demonstrate that the ESIPT of DEAHF likely happen more in [EMIm][NTf2] than in [BMIm][PF6]. The solvation effects in [BMIm][PF6] exhibit greater prominence compared to those in [EMIm][NTf2], as evidenced by the free energy curve. The alterations in dipole moment indicate a substantial solvation relaxation during the ESIPT processes. Our aforementioned research offers backing for the advancement of novel fluorescent probes.